The effect of pressure on the elastic constants of Cu, Ag and Au - Ciftci, Yasemin O.; Colakoglu, Kemal; Kazanc, Sefa; Ozgen, Soner (Versita, 2006)
This paper describes the effect of pressure on some the mechanical properties of transition metals Cu, Ag, and Au, such as elastic constants and bulk modulus. Using molecular dynamics (MD) simulation, the present study was carried out using the modified many-body Morse potential function expression in the framework of the Embedded Atom Method (EAM). The effect of pressure on equilibrium volume, elastic constants, and bulk modulus were determined, and found to be in agreement with other theoretical calculations and experimental data. (c) Versita Warsaw and Springer-Verlag Berlin Heidelberg. All rights reserved.
Keywords: molecular dynamics; transition metals; elastic constants